Remarks on Certain Selected Fixed Point Theorems - II - Kumar, Santosh (Kathmandu University Journal of Science Engineering and Technology, 2010)
Recent common fixed point theorems due to Kumar et al and Jungck are used to derive two common fixed point theorems for four finite families of mappings in complete and compact metric spaces respectively. AMS (MOS) Subject Classification(2000) : Primary 54 H 25; Secondary 47 H 10. Key Words and phrases: Compatible mapping; coincidentally commuting mappings; coincidence point; fixed point; common fixed point. DOI: 10.3126/kuset.v3i2.2894 Kathmandu University Journal of Science, Engineering and Technology Vol.3, No.2, August 2007, pp 27-30